Diagnostic Procedures and Prosthetic Management of Cemento-Osseous Dysplasia: A Case Report - ELQARFAOUI, Amina; AMINOU, Loubna; TALEB, Bouchra; MERZOUK, Nadia; REGRAGUI, Anissa (Integrative Journal of Medical Sciences, 2022)
Cement-osseous dysplasia is an uncommon benign fibro-osseous lesion of the maxillae in which cementum tissue replaces the normal architecture of the bone. It is usually asymptomatic, and its discovery is incidental at a routine radiological examination. Treatment is necessary if an infection develops due to exposure to the lesion in the oral cavity. In these severe cases, pain, cortical blowing, and facial deformity may be present. Thus, patients with cemento-osseous dysplasia have prosthetic bearing surfaces unfavorable for prosthetic rehabilitation. The management of cemento-osseous dysplasia requires a careful clinical examination to make a correct diagnosis and develop the appropriate treatment plan. The practitioner must inform the patient of the limitations of prosthetic rehabilitation. The objective of this article is to review, through a case report, the clinical, histological, and radiological characteristics and possible complications of this lesion and to highlight its impact on the prosthetic bearing surfaces and the problems inherent in prosthetic rehabilitation.